Pengaruh Persepsi Harga Dan Cita Rasa Produk Terhadap Keputusan Pembelian Pada Mie Bakso Cicim - Ayuda Nugraha; Suci Putri Lestari; Evilia Sri Yuniar (CV. ITTC INDONESIA, 2025)
This study aims to determine the effect of Price Perception and Product Taste simultaneously or partially on Purchasing Decisions on consumers of Mie Bakso Cicim Tasikmalaya. The method used in this study uses a quantitative method. With a research sample of 100 people as respondents. Sampling using non-probablility precisely using purposive sampling. And the analysis method used is multiple linear regression analysis, the results of the regression equation Y = 5.164 + 0.545X1 + 0.215X2 + e. Based on the results of the study, it shows that Price Perception is classified as Very Good, Product Taste is included in the Very Good classification, and Purchasing Decision is included in the Very Good classification. The test results show that simultaneously Price Perception and Product Taste have a significant effect on Purchasing Decisions. Partially, Price Perception has a significant effect on Purchasing Decisions and Product Taste has a significant effect on Purchasing Decisions.